Epithelioid inflammatory myofibroblastic sarcoma: the youngest case reported - Sajida Batool; Arvind Ahuja; Devender Singh Chauhan; Minakshi Bhardwaj; Atul Kumar Meena (University of São Paulo, 2021)
Epithelioid inflammatory myofibroblastic sarcoma (EIMS) is a rare variant of the inflammatory myofibroblastic tumor. It has an aggressive clinical course and a high rate of recurrence. EIMS primarily affects children and young adults. Hereby, we report this entity in a 4-month-old infant who presented with an abdominal mass. Imaging studies revealed a large hypodense mesentery-based lesion involving the right half and mid-region of the abdomen. The mass with an attached segment of the small bowel was excised in toto. Grossly, a large encapsulated tumor was identified arising from the mesentery of the small bowel. The histological examination showed a tumor consisting of epithelioid to spindle cells loosely arranged in a myxoid background with numerous blood vessels and lymphoplasmacytic inflammatory infiltrate. On immunohistochemistry, the tumor cells showed positivity for ALK1 (nuclear), desmin, SMA, CD68, and focal positivity for CD30. A final diagnosis of EIMS of the small intestine was rendered. To the best of our knowledge, this case is the youngest reported case in literature.